Handover analysis for multicast enabled network mobility management using network simulator - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Islam, Shayla (Science & Engineering Research Support Society (SERSC), 2017)
Network mobility management has become a popular topic in networking research due to its ability to mitigate mobile IPv6 problems. However the standard network mobility management does not support multicast traffic. Hence in this paper, we introduce context transfer and multicast fast reroute, to enable multicast in the standard network mobility management. This implementation enables multicast in network mobility management with high handover performance support. This paper evaluates handover performance for multicast enabled network mobility management using network simulator called NS3. NS3 is a network simulator that implements virtual network prototype. By using the virtual network entities provided by the NS3, the proposed network mobility management architecture is simulated and its activity is analyzed. The parameters used are referred to real network implementation.